2014
DOI: 10.1164/rccm.201310-1894oc
|View full text |Cite
|
Sign up to set email alerts
|

The Site and Nature of Airway Obstruction after Lung Transplantation

Abstract: Chronic lung allograft rejection is associated with a progressive form of constrictive bronchiolitis that targets conducting airways while sparing larger airways as well as terminal bronchioles and the alveolar surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 22 publications
5
71
0
Order By: Relevance
“…An earlier report from our laboratories analysed explanted lungs of patients with the BOS clinical phenotype of CLAD [13] and showed no difference in the total number of visible airways and terminal bronchioles between BOS and control lungs. However, a reduction in the lumens of the smaller bronchi and pre-terminal bronchioles by a constrictive process could be observed.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…An earlier report from our laboratories analysed explanted lungs of patients with the BOS clinical phenotype of CLAD [13] and showed no difference in the total number of visible airways and terminal bronchioles between BOS and control lungs. However, a reduction in the lumens of the smaller bronchi and pre-terminal bronchioles by a constrictive process could be observed.…”
Section: Introductionmentioning
confidence: 79%
“…The protocol for processing and sampling the lung specimens has been described in detail elsewhere [13,15]. Briefly, each lung was inflated with air to a transpulmonary pressure of 30 cmH 2 O, and then deflated to 10 cmH 2 O and held in that position while they were frozen solid in liquid nitrogen vapour and stored at −80°C.…”
Section: Specimen Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of azithromycin changed the field and allowed to differentiate BOS in a neutrophilic phenotype, which may be responsive to azithromycin treatment, and a non-neutrophilic phenotype that is very difficult to treat and usually does not respond to azithromycin. This last phenotype is indeed characterized by fibrotic plugging of the preterminal bronchioles, but in addition shows limited areas of complete collapse of airways, without any overt intraluminal fibrosis nor inflammation being present [20]. As a consequence, it seems acceptable that treatment of inflammation does not improve the pulmonary function in all patients.…”
Section: Expert Opinionmentioning
confidence: 99%
“…a reduced synthesis of matrix proteins upon IL-1α activation, challenges this view of IL-1α as a profibrotic mediator. Thus, whether IL-1α is involved in the loss of small conducting airways or in peribronchial fibrosis observed in COPD [21] remains unclear. In cancer, BAE et al [22] showed that IL-1α may enhance oral squamous carcinoma-associated fibroblast proliferation through the secretion of CCL7, CXCL1 and IL-8/CXCL8 chemokines.…”
mentioning
confidence: 99%